Fear of missing out among adolescents: Formulating big five personality traits to smartphone addiction - Fauzi, M. A.; Kasim, Nur Muneerah; Paiman, Norazha (IGI Global, 2021)
Smartphone use has changed the landscape of technology. People are more concerned with their smartphone use than being physically attached to their surroundings, which has led to scholars on studies in smartphone addiction. This study aims to understand the link between personality traits of young adolescents and fear of missing out in relation to smartphone addiction. A partial least square structural equation modelling (PLS-SEM) is applied in testing the proposed hypotheses relationship. A total of 210 respondents consisting of young adolescents, primarily higher education students, participated in the study. It was discovered that among the five personality traits, extraversion and neuroticism were found to be significant on fear of missing out. While fear of missing out has the most significant influence on adolescent smartphone addiction, implications towards theoretical and managerial aspects are discussed and elaborated.